Interdisciplinaridade crítico-transformadora: utopia ou possibilidade? - Freitas, Wélica Patricia Souza de (2023)
In recent years, in the Brazilian context, the emergence of discussions about interdisciplinarity and teacher training has been revealed. However, researchers in the field highlight the shortcomings that still surround these approaches. In relation to teacher training, the obstacles are related to deficiencies in the initial and continuing dimensions and the working conditions of teachers that make it difficult to insert interdisciplinarity in the school context. Added to this issue is the lack of understanding of this approach on the part of teachers, as well as the lack of a methodology that provides support for interdisciplinary work. In this scenario, the Islands of Interdisciplinary Rationality (IIR) methodology can be considered as a possibility for approaching interdisciplinarity. Given this conjecture, our investigation intends to build theoretical and methodological support for interdisciplinarity in a critical-transformative bias for the training of science teachers. Qualitative in nature, our research is structured in two dimensions. The first encompasses the analysis of theses and dissertations via Discursive Textual Analysis (DTA) in which we seek to weave understandings about what is shown in research that addresses the IRI methodology in/for the training of science teachers. In this proposition, some clues gave us the opportunity to glimpse comprehensive nuances regarding the IRI methodology in the training of science teachers, namely, the importance of training based on a critical bias, the problematization of the concrete problem, as well as the need to approach a Scientific and Technological Literacy (STL) in a broader perspective to enable the empowerment of teachers and students. As emerging understandings, we signal the necessary inseparability between the IRI methodology and STL. In addition to the need for (re)significations for teacher training, which encompasses the objectives of STL. Through the analysis carried out, we were able to verify the emergence of training practices that break with the bias of technical rationality, in order to give meaning to the role of being a teacher, not just reducing them to the role of mere curriculum executors or “class givers”. In this way, we defend the training model of teachers as transformative intellectuals. Furthermore, we were able to gain some understanding about the characteristics of the concrete problem in the IRI methodology. Some clues manifested in our analysis scenario enabled us to understand that the concrete problem needs to present the same essence as the generating themes, in order to provide subjects with a critical reading of reality. In this context, such comprehensive biases contributed to the construction of the second dimension of this study, which consists of the elaboration of a theoretical and methodological proposal for an interdisciplinary approach based on a critical-transformative bias. To this end, a possibility of intertwining between the theoretical assumptions of Gérard Fourez, Paulo Freire's liberating pedagogy, and some aspects of Henry Giroux's critical theory is presented. Such approaches are centered on four axes, namely: understanding literacy and STL, problematization, the role of the school and the role of the educator. In this way, we present a methodological essay for critical-transformative interdisciplinarity supported by six moments, obtaining the generating theme, problematization, perception achieved, theoretical enrichment, critical perspective and concrete transformative action. The understandings provided provided us with elements to answer the title question of this thesis, “transformative critical interdisciplinarity: utopia or possibility?” The understandings woven throughout the study indicate that such an interdisciplinary approach can become a possibility, requiring actions and research that restructure training and teaching work in order to enhance a critical-transformative direction.